News Recommendations from Social Media Opinion Leaders: Effects on Media Trust and Information Seeking. Issue 5 (1st June 2015) - Turcotte, Jason; York, Chance; Irving, Jacob; Scholl, Rosanne M.; Pingree, Raymond J.
Abstract: Polls show a strong decline in public trust of traditional news outlets; however, social media offers new avenues for receiving news content. This experiment used the Facebook API to manipulate whether a news story appeared to have been posted on Facebook by one of the respondent's real-life Facebook friends. Results show that social media recommendations improve levels of media trust, and also make people want to follow more news from that particular media outlet in the future. Moreover, these effects are amplified when the real-life friend sharing the story on social media is perceived as an opinion leader. Implications for democracy and the news business are discussed.